STUDENTS’ PARTICIPATION IN THE DECISION-MAKING PROCESS IN THE GHANAIAN TERTIARY INSTITUTIONS - Owusu, Benjamin Boampong; Nyame, Festus (Journal of Education and Practice, 2022)
Purpose: The study's purpose was to determine the extent of student participation in decision-making in higher institutions and the advantages it offers both students and the university administration. At Kwame Nkrumah University of Science and Technology (KNUST), the purpose of the study was to identify the barriers to full student participation in decision-making. Methodology: A quantitative approach was used in this study. The study used descriptive survey and sampled 136 out of 150 people that were the target group. Questionnaire was used to collect data which were analysed with SPSS statistical package (version 25). Descriptive statistics were used to present the data. Findings: Findings indicate that student engagement in decision-making at the university was either little or nonexistent at all levels. Administrators are consistent in their opinions, however, students appeared to hold differing opinions. Administrators concur with the idea that student input should be greater in university governance to some level. The findings further indicate that student participation in institutional decision-making is confirmed by the students' current standing in university governance. Unique contribution to theory, practice and policy: The Student Representative Council (SRC) needs to re-examine the functions and roles in light of current global trends. Where necessary, changes should be instituted to improve student contribution to university decision-making. In light of current global developments, the Student Representative Council (SRC) has to review its tasks and responsibilities. Changes should be implemented as needed to increase student input into university decision-making.